1992
DOI: 10.1139/v92-343
|View full text |Cite
|
Sign up to set email alerts
|

Coordination chemistry of thioether–pyridazine macrocycles II. Synthesis, structural and spectroscopic studies of dinuclear copper(II) and polynuclear copper(I) and silver(I) complexes of a tetrathiapyridazinophane macrocyclic ligand

Abstract: . Can. J. Chem. 70,2709Chem. 70, (1992. The preparation and properties of the thioether-pyridazine macrocycle (L3; Cl,H16N2S4) containing one pyridazine subunit, and its copper(II), copper(I), and silver(1) complexes are described. Magnetic susceptibility data (5-300 K) for the binuclear complexes [CuL3Cl2I2 (I) and [CuL3Br2I2 (11) have been fitted to the Friedberg magnetization expression with a molecular field correction. Intradimer antiferromagnetic exchange is weak (-25 < 18 cm-I), with even weaker interd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Although some few reports deal on the construction of coordination compounds assembled by thioether ligands bound to the harder Cu(II) ion [59][60][61][62], we are not aware of any 3D material of this type. In light of the application of Cu(II)-containing materials in the domain of molecular magnetism [63][64][65][66], the crystal engineering of 3D materials combining the paramagnetic Cu(II) salts and organosulfur ligand appears as interesting perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Although some few reports deal on the construction of coordination compounds assembled by thioether ligands bound to the harder Cu(II) ion [59][60][61][62], we are not aware of any 3D material of this type. In light of the application of Cu(II)-containing materials in the domain of molecular magnetism [63][64][65][66], the crystal engineering of 3D materials combining the paramagnetic Cu(II) salts and organosulfur ligand appears as interesting perspective.…”
Section: Resultsmentioning
confidence: 99%
“…This band shifts 8-23 cm-' to lower energy in all the complexes (Table 8), suggesting the coordination of pyridazine rings (28,29). With ligands L1 and L2 sulfur coordination was accompanied by a small shift in this band to higher energy (1-2 cm-I), while for nitrogen coordination shifts to lower energy were observed (-5 to -1 1 cm-I) (28).…”
Section: Spectroscopy and Magnetismmentioning
confidence: 87%
“…However, our initial studies in this area, which have involved the syntheses and structural and spectroscopic studies of a series of copper(II), copper(I), and silver([) complexes of thioetherpyridazine macrocycles containing one, two, and three pyridazine subunits (L3, L2, L1, Fig. 1 ) (28,29), have shown that, so far, simultaneous intraligand NS coordination does not occur. The present paper describes the copper coordination chemistry of the 2 : 2 macrocyclic ligand L4 (Fig.…”
Section: Vs Sce) Reductionmentioning
confidence: 99%
“…L6 to H 2 L12, Figure 5). [55,56,59,64Ϫ66] Figure 5. A selection of thioether pyridazine-and phthalazine-containing macrocycles Initially both [2ϩ2] and [3ϩ3] thioether macrocycles were obtained from the reaction of 3,6-dichloropyridazine and 1,3-propanedithiol (L6 and L7, Figure 5): these macrocycles were separated from one another readily on the basis of solubility.…”
Section: Macrocyclic Pyridazine and Phthalazine Ligandsmentioning
confidence: 99%
“…A selection of thioether pyridazine-and phthalazine-containing macrocycles Initially both [2ϩ2] and [3ϩ3] thioether macrocycles were obtained from the reaction of 3,6-dichloropyridazine and 1,3-propanedithiol (L6 and L7, Figure 5): these macrocycles were separated from one another readily on the basis of solubility. [56] Other dithiols employed in the cyclisation with 3,6-dichloropyridazine included 3,7-dithianonane-1,9-dithiol, [55] 2,2Ј-thiodiethanethiol (L10, Figure 5), [64,65] and 1,4,7,10-tetrathiadecane. [65] Some [2ϩ2] phthalazine analogues were prepared by reaction of 1,4-dichlorophthalazine with 1,3-propanedithiol (L8, Figure 5), 3,7-dithianonane-1,9-dithiol (L9, Figure 5) or 2,2Ј-thiodiethanethiol.…”
Section: Macrocyclic Pyridazine and Phthalazine Ligandsmentioning
confidence: 99%